Types of Electronic Resources And Possibilities Of Their Use in the Education Of vocational Schools (Eurasian Scientific Herald, 2023)
Nowadays, e-learning is a set of tools that implement interesting and developmental functions that have full opportunities for independent learning. In this work, recommendations are given for e-learning resources to create a need and interest in issues and assignments that create problematic situations.